2022
DOI: 10.3390/ma15227891
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Solidification Effect of Dredger Fill by Microbial-Induced Calcium Precipitation (MICP)

Abstract: This paper puts forward a new soft soil reinforcement technology—microbial-induced calcite precipitation (MICP) technology—which considers the problem of dredger fill soft-soil reinforcement in Dalian Taiping Bay. In this paper, the calcium carbonate content (CCC) and unconfined compressive strength (UCS) of microbial solidified dredger fill (MSDF) samples were determined using laboratory experiments. The microstructure and chemical composition of MSDF samples were studied by SEM–EDS and XRD. The failure and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
0
0
0
Order By: Relevance
“…Initially, εv experienced shear contraction followed by shear dilation, leading to larger εv values and weaker shear dilation behavior compared to the conventional triaxial tests. (5) The enhanced modified Cambridge model, featuring its adjusted curve, closely mirrors the curves derived from true triaxial tests. It adeptly characterizes the stressdeformation response of the soil subjected to three-dimensional stress circumstances, offering a robust theoretical foundation for the practical implementation of lightweight stabilized soil in engineering projects.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Initially, εv experienced shear contraction followed by shear dilation, leading to larger εv values and weaker shear dilation behavior compared to the conventional triaxial tests. (5) The enhanced modified Cambridge model, featuring its adjusted curve, closely mirrors the curves derived from true triaxial tests. It adeptly characterizes the stressdeformation response of the soil subjected to three-dimensional stress circumstances, offering a robust theoretical foundation for the practical implementation of lightweight stabilized soil in engineering projects.…”
Section: Discussionmentioning
confidence: 77%
“…Lei et al [4] employed anionic polyacrylamide to treat solidified soil. Li et al [5] conducted an innovative investigation on soft soil stabilization in hydraulic fill using microbial-induced calcium carbonate precipitation. Soganci et al [6] utilized slag as a solidifying agent for soft clay and investigated the solidification effect when combined with marble dust.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the solidification effect of the soil was influenced by various factors, including colony distribution, initial concentration of the bacterial solution, and standing time [18][19][20][21]. Moreover, they expanded the application of MICP technology to silty sand [22], expansive soil [23], dredger fill [24], and other types of soil solidification. Further research indicates that soil properties are closely linked to the crystal type and calcium carbonate content, which directly impacts the soil's reinforcement effect.…”
Section: Introductionmentioning
confidence: 99%